Boosting Fiscal Space : The Roles of GDP-Linked Debt and Longer Maturities - Ostry, Jonathan (Departmental Papers; Departmental Paper ;, 2018)
Noting that the aftermath of the global financial crisis has left many advanced economies with very high sovereign debt ratios and some emerging markets with high debt, this report considers whether there are ways to expand fiscal space that do not involve countries paying down debt or promising to do so in the future, to make fiscal consolidation more growth-friendly. It explains that policymakers argue that their fiscal space is limited and that it would be difficult to take advantage of the opportunity of low interest rates to undertake fiscal expansion, and it considers a ways to raise fiscal space that does not require contractionary fiscal policy and whether there is a way to make fiscal consolidation more growth-friendly to produce larger gains in fiscal space. It argues that debt management policies may provide an answer to expanding fiscal space for a given path of primary fiscal balances by reducing the risk that a sovereign may default in bad states and generate a payoff in terms of reduced to real borrowing costs. It describes two debt management policies: issuance of GDP-linked debt and issuance of longer maturity bonds, as opposed to short-term debt. It focuses on the effect of these debt management policies on real borrowing costs and default risk for the sovereign and details the literature on GDP-linked debt and the maturity structure and how the report fills gaps in the literature; how uncertainty affects fiscal space and how debt management can play a role in increasing it, with estimates and simulations of potential gains in fiscal space flowing from debt management; and the sensitivity of the findings to underlying assumptions and policy implications.